2019
DOI: 10.1007/978-3-030-19591-5_27
|View full text |Cite
|
Sign up to set email alerts
|

Game-Based Human-Robot Interaction Promotes Self-disclosure in People with Visual Impairments and Intellectual Disabilities

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The use of robots was also mentioned. It could be interesting to study the role of robots in entertainment and exercise, as well as in improving psychological wellbeing, as in the explorative study by De Groot et al [19]. Several pilot studies evaluating the efficacy of specific sensor applications for the care of persons with visual-or visual-and-intellectual disabilities could be carried out based of the results of this study.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…The use of robots was also mentioned. It could be interesting to study the role of robots in entertainment and exercise, as well as in improving psychological wellbeing, as in the explorative study by De Groot et al [19]. Several pilot studies evaluating the efficacy of specific sensor applications for the care of persons with visual-or visual-and-intellectual disabilities could be carried out based of the results of this study.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…ref. [20,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]); however, evidence is limited regarding how people's subjective perceptions of self-disclosure align with objective measures of self-disclosure. Here we evaluate both people's perceptions and their actual disclosures across three experiments.…”
Section: Subjective and Objective Disclosurementioning
confidence: 99%
“…The results of a previous pilot study confirmed that clients with visual and intellectual disabilities had positive initial responses to the robot, were able to engage in a meaningful conversation with the robot, and enjoyed the interaction (De Groot, Barakova, Lourens, van Wingerden, & Sterkenburg, 2019 How do persons with visual and intellectual disabilities experience therapy sessions with a robot? Can the robot assist in teaching persons with visual and intellectual disabilities useful coping strategies to reduce worrying? Does the robot elicit empathy and emotion‐related responses from the participants? …”
Section: Introductionmentioning
confidence: 65%
“…The results of a previous pilot study confirmed that clients with visual and intellectual disabilities had positive initial responses to the robot, were able to engage in a meaningful conversation with the robot, and enjoyed the interaction (De Groot, Barakova, Lourens, van Wingerden, & Sterkenburg, 2019 1. How do persons with visual and intellectual disabilities experience therapy sessions with a robot?…”
Section: The Current Studymentioning
confidence: 70%